Short-time alkaline peroxide pretreatment for rapid pulping and efficient enzymatic hydrolysis of rice straw. (April 2017) - Hideno, Akihiro
Highlights: Rapid pulping was achieved by short-time AP treatment of rice straw. High enzymatic digestibility was obtained from the short-time AP-treated rice straw. Microfibril networks and nano-scale pores were observed on the surface of AP-treated rice straw. Abstract: To improve utilization of agricultural residues in biorefineries, the effects of alkaline peroxide (AP) pretreatment on thermal degradation and enzymatic digestibility of rice straw were investigated. A high-cellulose (>70%) pulp with a width of a few micrometers was obtained by rapid (10 min) treatment with AP, without prior heating or other treatment. Moreover, enzymatic hydrolysis of the pulp produced a high glucose yield (approximately 80%). Microfibril networks were exposed, and many nano-scale pores that are easily penetrated by cellulases were observed on the surface of the AP-treated sample. For enzymatic hydrolysis of the pulp, increasing the dosage of cellulases was more effective for improving the glucose yield than addition of a grinding treatment. This AP treatment has the potential for on-site application because it is simple, highly efficient, and can be performed in a short time.